Modernization of the PGU-450 thermal circuit with an increase in the thermal power of heating selections and preservation of the total electric power - Zverev, L. O.; Zlobin, V. G.; Zvereva, E. R. (Izvestiâ vysših učebnyh zavedenij. Problemy ènergetiki, 2024)
PURPOSE. Modernization of the PGU with an increase in thermal power and preservation of electrical power using a block afterburning device (BDU) in a heat recovery boiler (CU). METHODS. Comparative studies of the characteristics of the PGU-450 without a BDU and with an installed DBU were conducted results. As a result of comparative studies of the main characteristics of the PGU-450 and the main characteristics of the PGU-450 before and after installation of the DBU in recovery boilers, it was shown that the use of the BDU effectively solves the problem of covering peak thermal loads in the transition periods of the OSP (spring – summer; autumn – winter); the possibility of long-term operation of the BDU during the entire period of operation of the PG unit is shown; it is revealed that it is most advisable to implement the BDU on the PGU blocks for which the obligations under the DPM agreements have expired. By increasing the electric power by 6% (in the heating mode), the payment for power in the KOM market increases; an increase in the electric power of the PGU unit when operating in condensation mode by 11% minimizes the under-supply of power to the OREM at outdoor temperatures above + 15 degrees; Despite a 3% increase in URUE to 190 g/kWh, the electric energy produced remains competitive in the OREM. CONCLUSION. Thus, as a result of the research, it was shown that when the DBU is switched on, the thermal power of the PGU-450 increases to 320 Gcal/hour, which makes it possible to cover the missing thermal power. Thus, the operation of the T-250 in a mode close to condensation with an URUT ee of 350 g / kWh is excluded, and the entire thermal load is covered by the PGU-450, but with a slightly degraded URUT ee of 190 g / kWh. Such a composition of the CHP equipment ensures the maximum possible economic efficiency of the plant in the electricity market with full coverage of heat consumption.